Assessment of resilience of aromatic plants during the COVID-19 pandemic in Douala, Cameroon - Mvogo Ottou, Patrice Brice Brice; Fogang, Christian Wilson Saagu; Ndiang, Zenabou; Biyon, Jacques Bruno Ngotta; Mokake, Seraphine Ebenye; Mbezo, Fidèle Bemadoum; Betti, Jean Lagarde; Ndongo, Din; Priso, Richard Jules (Journal of Drug Delivery and Therapeutics, 2022)
Aromatic plants are one of the components of Cameroonian medicinal flora that seem to be an alternative to fight against the Covid-19 disease. The present study aims to establish chemical characterization of some aromatic plant organs used in the Douala IV sub-division during the COVID-19 pandemic. A semi-structured survey was carried out between September and December 2020 in order to identify aromatic plants used for health diseases during the Covid-19 pandemic. Due to their ethnobotanical index the selected plants were screened chemically through staining and precipitation methods to determine different bioactive compounds. Thirty-one (31) plant species belonging to 17 families were recorded with the dominated by Lamiaceae and Zingiberaceae being the dominant families and Ocimum gratissimum as the most cited species (28.57%) in the composition of recipes. Leaves (50.80%) were the most used organs to prepare the decoctions (33.33%) administered to patients orally. These plants were used in the treatment of 51 ailments diseases, notably malaria, cough and typhoid fever with 22, 21 and 12 citations respectively. Informant Consensus Factors (ICF) showed a relatively high agreement (0.75) for the use of species against respiratory diseases. Zingiber officinale, Citrus limon and Cymbopogon citratus had a good performance (Ip = 3) against cough, typhoid and malaria respectively. Extracts of aromatic plant organs were rich in alkaloids and phenolic compounds. These aromatic species showed their ability to treat respiratory and other infectious diseases, and could be an alternative to fight against Covid-19. Keywords: Aromatic plants; Bioactive compounds; Douala IV; Drug recipes; Ethnobotanical index.